Keluhan Muskuloskeletal Akibat Penggunaan Gawai pada Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Selama Pandemi COVID-19 - Batara, Graysela O.; Doda, Diana V. D.; Wungow, Herlina I. S. (JURNAL BIOMEDIK : JBM, 2021)
Abstract: During the covid-19 pandemic, there was a change in the routine of daily activities, including the increasing use of smartphones. Based on previous research, the use of devices can cause musculoskeletal complaints. This study aims to determine the prevalence of musculoskeletal complaints due to the use of devices and to evaluate the relationship between musculoskeletal complaints and the use of smartphones in college students. This study is a cross-sectional study using a demographic questionnaire, modified Nordic Body Map, and Ovako Work Posture Analysis System. Statistical analysis using the Spearman correlation. There were 183 respondents (n=183). Most of the musculoskeletal complaints were in the neck (n=92; 50.3%), shoulders (n=76; 41.5%), upper back (n=63; 34.4%) and lower back (n=63; 34.4%). Most of the pain was categorized as mild pain. The Spearman correlation test showed significant correlations, as follows: between musculoskeletal complaints in the shoulder (p=0.000) and arm (p=0.045) with the duration of learning; between musculoskeletal complaints in the elbow and duration of social media (p=0.027); between musculoskeletal complaints in the upper back (p=0.042) dan low back (p=0.023) with the duration of learning. Most of the risk assessment of musculoskeletal complaints based on body posture when using a smartphone is a medium category that needs improvement.Keywords: musculoskeletal complaints, smartphone, duration, frequency, body postureÂ Â Abstrak: Selama masa pandemi covid-19, terjadi perubahan rutinitas aktivitas sehari-hari diantaranya penggunaan telepon cerdas yang meningkat. Berdasarkan penelitian sebelumnya penggunaan gawai dapat menyebabkan keluhan muskuloskseletal. Penelitian ini bertujuan untuk mengetahui prevalensi keluhan muskuloskeletal akibat penggunaan gawai dan mengevaluasi hubungan antara keluhan muskuloskeletal dengan penggunaan telepon cerdas pada mahasiswa. Penelitian ini merupakan penelitian potong lintang dengan menggunakan kuesioner demografi, modifikasi Nordic Body Map dan Ovako Work Posture Analysis System. Analisa statistik menggunakan korelasi Spearman. Hasil penelitian menggunakan 183 responden (n=183). Keluhan muskuloskeletal yang sering dirasakan yaitu keluhan pada leher (n=92; 50.3%), bahu (n=76; 41.5%), punggung atas (n=63; 34.4%) dan punggung bawah (n=63; 34.4%). Karakteristik nyeri yang sering dialami yaitu nyeri ringan. Uji korelasi Spearman mendapatkan korelasi bermakna antara: keluhan muskuloskeletal pada bahu (p=0.000) dan lengan (p=0.045) dengan durasi pembelajaran; keluhan muskuloskeletal pada siku dengan durasi media sosial (p=0.027); serta keluhan muskuloskeletal pada punggung atas (p=0.042) dan punggung bawah (p=0.023) dengan durasi pembelajaran. Penilaian risiko keluhan muskuloskeletal berdasarkan postur tubuh saat menggunakan telepon cerdas paling sering di alami yaitu kategori medium yang perlu dilakukan perbaikan postur tubuh.Kata kunci: keluhan muskuloskeletal, telepon cerdas, durasi, frekuensi, postur tubuh